Global patterns and predictors of C:N:P in marine ecosystems - Tatsuro Tanioka; Catherine A. Garcia; Alyse A. Larkin; Nathan S. Garcia; Adam J. Fagan; Adam C. Martiny (Communications Earth & Environment, 2022)
Variations in the biogeography of particulate organic matter carbon-nitrogen-phosphorus stoichiometry in the surface ocean can be robustly predicted by different factors depending on latitude, region and hemisphere, according to a global ocean observational analysis.